Effect of sire breed and rearing system on growth, carcass composition and meat traits of Cinta Senese crossbred pigs - Riccardo Bozzi; Gustavo Campodoni; Anna Acciaioli; Francesco Sirtori; Alessandro Crovetti; Carolina Pugliese; David Meo Zilio; Oreste Franci (Italian Journal of Animal Science, 2011)
The objective of this work was to evaluate, under indoors and outdoors rearing, the effect of crossing Cinta Senese (CS) with Italian Large White (ILW) and Italian Duroc (ID) breeds. Starting from 72 d of age, 9 CS, 8 ILWxCS and 7 IDxCS were reared outdoors (OUT) in 3 paddocks of 2 ha and 8 CS, 10 ILWxCS and 8 IDxCS pigs were reared indoors (IN) in three pens of 20 m2. All pigs, fed the same commercial diets, were weighed and measured periodically and were slaughtered at a target live weight of 150 kg. Indoor-pigs grew faster than the outdoor ones and crossbred pigs showed higher average daily gain than CS breed (476, 437 and 387 g/d for IDxCS, ILWxCS and CS, respectively). Rearing system had moderate or null effect on carcass and sample cut composition whereas the OUT pigs, when compared to IN ones, showed higher moisture and lower IMF in Longissimus L. and Psoas M. muscles and higher cooking loss of meat (22.1 vs 18.4 %) that resulted also less red (a* 10.94 vs 12.04). CS had more fat in carcass and more bone in sample cut than the crossbreeds. ILWxCS showed lower IMF content and higher moisture in muscles and brighter and less red meat than the other breeds, while IDxCS produced the most tender meat after cooking. The use of Italian Duroc could be profitable on Cinta Senese to improve the farming performance without worsening the fresh meat quality.